Ответы и объяснения

2012-12-10T10:16:37+00:00

А(2 1 -3)    В(6)

   0 3 1          4

   1 2-2          1

находим главный опредилитель

|2 1-3|

|0 3 1|=2*3*(-2)+0+1*1*1-1*3*(-3)-2*1*2-0=-12+0+1+12-4-0=-4

|1 2-2|

находим дельта 1

|6 1-3|

|4 3 1|=6*3*(-2)+(-3)*4*2+1*1*1-1*3*(-3)-6*1*2-1*4*(-2)=-54

|1 2-2|

находим дельта 2

|2 6-3|

|0 4 1|=2*4*(-2)+0+6*1*1-1*4*(-3)-2*1*1-0=-24

|1 1-2|

находим дельта 3

|2 1 6|

|1 3 4|=2*3*1+6*1*2+1*4*0-0*3*6-2*4*2-1*1*1=1

|0 2 1|

x=-54/-4=13,5 ; у=-24/-4=6 ;z=1/-4=-0,25